A3.09 Synovial fibroblasts as determinants for arthritis specific pattern of joint involvement. (24th February 2016) - Frank-Bertoncelj, M; Klein, K; Russo, G; Bratus, A; Karouzakis, E; Kolling, C; Filer, A; Buckley, CD; Gay, RE; Gay, S; Ospelt, C
Abstract : Background and objectives: Most forms of arthritis occur with a distinctive pattern of joint involvement. To elucidate whether stromal differences between the joints might play a role in the susceptibility of joints to develop arthritis, we compared the transcriptome, epigenetic marks and functions of synovial fibroblasts (SF) isolated from different joints. Material and methods: SF were isolated from hand, shoulders, and knees from RA and OA patients. Total RNA was isolated and sequenced on theIlluminaHiSeq 2000 (n = 21). Epigenetic regulation was studied by methyl-DNA -immunoprecipitation and treatment with bromodomain inhibitors. Adhesion to tissue culture plates (n = 20) and proliferation (n = 15) were measured with the xCELLigence-RTCA-DP Instrument. Transwell plates were used to measure migration of leukocytes from healthy donors towards supernatants of cultured SF (n = 14). Results: Based on their transcriptome profile, SF clustered according to their joint of origin. Hand SF featured increased expression of transcripts in the HOX cluster that are also increased in distal limb buds during embryonic development, eg, HOXD13, HOXA13 and HOTTIP. Accordingly, genes upregulated in hand SF were clustered in biological processes such as 'limb development' (enrichment score (ES) 4.3) and 'tissue morphogenesis' (ES 3.4). The expression of these developmental transcripts in adult SF was maintained by histone acetylation and lack of DNA methylation. Other biological processes enriched in hand SF were 'cell-cell signalling' (ES 2.9), 'cell migration' (ES 1.9) and 'defense response' (ES 0.9). Genes that were lower expressed in hand SF were mainly enriched in 'cell adhesion' (enrichment score 2.3) and 'embryonic morphogenesis (enrichment score 2.3). Functionally adhesion was significantly lower in handcompared to shoulder SF (cell index 0.6 ± 0.2 vs. 0.9 ± 0.2, p = 0.01). Hand SF proliferated faster than shoulder SF (doubling time: 39 ± 3h vs. 67 ± 15h, p = 0.03) and significantly more leucocytes migrated towards the supernatants from cultured hand SF than shoulder SF. Conclusions: SF from different anatomic locations exhibit significant differences in their transcriptome, particularly in the expression of embryonic transcription factors encoded in the HOX cluster. Hand SF display differences in their chemotactic, proliferative and adhesive properties, which may explain why chronic arthritidis tend to be more destructive in hands compared to other joints.